A human retrieval study of plasma-sprayed hydroxyapatite-coated plateau root form implants after 2 months to 13 years in function - Coelho, Paulo G.; Bonfante, Estevam A.; Marin, Charles; Granato, Rodrigo; Giro, Gabriela [UNESP]; Suzuki, Marcelo (Begell House, 2010)
Calcium phosphate-based bioactive ceramics in various physical and chemical formulations have been extensively utilized as biomaterials for bone regeneration/conduction. However, the determination of their in vivo temporal behavior from the short to long term in humans has been a challenge due to the lack of physical reference for morphologic and morphometric evaluation. The present study evaluated bone morphology and morphometry (bone-to-implant contact [BIC]) around plasma-sprayed hydroxyapatite (PSHA)-coated endosseous implants that were retrieved due to prosthetic reasons while successfully in function at the posterior region of the jaws from as early as 2 months to ~13 years after a 6-month healing period after placement. Bone morphology was evaluated by light microscopy, and BIC was determined using computer software. Irrespective of the time in vivo, lamellar bone was observed in close contact with the implant PSHA-coated surface and between plateaus. BIC ranged from ~35-95%, was highly directional, and Haversian-like osteonic morphology between plateaus was observed for most implants. The PSHA coating was present with little variation in thickness between the samples retrieved regardless of time in vivo. © 2010 by Begell House, Inc.
Keywords: Dental implant; Histology; Human; In vivo; PSHA; Retrieval; Bioactive ceramic; Bone morphology; Bone regeneration; Bone-to-implant contact; Chemical formulation; Endosseous implant; In-vivo; Morphometry; Temporal behavior; Biological materials; Calcium phosphate; Dental prostheses; Hydroxyapatite; Morphology; Plasma spraying; Bone; hydroxyapatite; plasma sprayed hydroxyapatite; unclassified drug; computer program; human; in vivo study; material coating; microscopy; morphometrics; plasma; tooth implantation